Evaluation of Morphine-Sparing Efficacy with Low-Dose Ketamine in Pediatric Postoperative Pain: A Pilot Randomized Controlled Trial - Naim Ismail Imunu; Isngadi; Rudy Vitraludyono; Arie Zainul Fatoni (HM Publisher, 2026)
Postoperative pain management in the pediatric population requires a delicate balance between effective analgesia and the minimization of opioid-related adverse events, particularly respiratory depression. While multimodal analgesia is the standard of care, the optimal dose-reduction potential of opioids when combined with N-methyl-D-aspartate (NMDA) antagonists remains undefined. We conducted a prospective, single-center, pilot randomized controlled trial using a double-blind observer protocol. Twenty pediatric patients aged 2 months to 7 years undergoing elective surgery were randomized into four groups. The control group (Group M) received standard continuous morphine at 0.33 µg/kg/min. Three intervention groups received fixed low-dose ketamine at 0.33 µg/kg/min combined with tapered morphine doses: Group KM-1 at 0.23 µg/kg/min, Group KM-2 at 0.16 µg/kg/min, and Group KM-3 at 0.06 µg/kg/min. The primary outcome was analgesic efficacy assessed by FLACC scores at 24 hours. Secondary outcomes included hemodynamic stability and rescue analgesia requirements. Baseline characteristics were comparable across groups. At 24 hours, the median FLACC scores were comparable between the high-dose control (Median 2.0; Interquartile Range 1.5–2.0) and the lowest morphine group (Group KM-3: Median 2.0; Interquartile Range 1.5–2.0; p = 0.438). Group KM-3 achieved an 81% reduction in morphine consumption with a 0% rescue analgesia rate, identical to the control group. In conclusion, preliminary data from this pilot study suggest that low-dose ketamine may permit a substantial reduction in morphine dosage of up to 81% without compromising analgesic efficacy. These findings warrant confirmation in larger, fully powered multicenter trials.